Bohemians in Taipei the life of theatre - Public Television Service ([Taiwan] : Public Television Service, 2004)
Passion. The very word evokes images of dedication, sacrifice, and love. Taipei's Bohemians tells of people who share a pasion for the theater. The theater is the tie that binds these disperate figures together. When the stage calls, they immediately drop what thay are doing and respond. That the pay the theater offers is meager in the extreme does not prevent these unconventional city dwellers from holding themselves to the most exacting artistic standards
DVD Format
Keywords: Theater -- China; Taipei's Bohemians